2017
DOI: 10.1128/genomea.00285-17
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Draft Genome Sequence of Rhizobium sp. Strain LCM 4573, a Salt-Tolerant, Nitrogen-Fixing Bacterium Isolated from Senegalese Soils

Abstract: The genus Rhizobium contains many species that are able to form nitrogen-fixing nodules on plants of the legume family. Here, we report the 5.5-Mb draft genome sequence of the salt-tolerant Rhizobium sp. strain LCM 4573, which has a G+C content of 61.2% and 5,356 candidate protein-encoding genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Rhizobium sp. is a type of strain with nitrogen fixation [42] that has the capacity to convert atmospheric dinitrogen (N2) to a reduced form, and provide more nitrogen for plant growth. Rhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobium sp. is a type of strain with nitrogen fixation [42] that has the capacity to convert atmospheric dinitrogen (N2) to a reduced form, and provide more nitrogen for plant growth. Rhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bacteroidetes belonged to one of the dominant denitrifiers that had a capacity for the reduction of NO 3 − -or NO 2 − -N to N 2 as the end product in paddy soils, which increased soil TN, especially NO 3 − -N loss through surface runoff from paddy fields (Table 5) [54]. Proteobacteria was abundant and mainly included free-living N-fixing β-Proteobacteria [55], which provided an efficient N source for paddy soils and thus increased N runoff loss (Table 5). Conversely, Chloroflexi belonged to green bacteria, which was a diverse group of chlorophototrophic organisms.…”
Section: The Influence Of Environmental Factors On Nitrogen and Phosphorus Lossesmentioning
confidence: 99%
“…Relevant literatures showed that species belonging to Rhizobium and Rhodobacter could degrade azo dyes and other aromatic compounds (Bin et al., 2004; Huang et al., 2016; Ruiz‐Arias et al., 2010; Song, Zhou, Wang, Yan, & Du, 2003). Some of them were even halotolerant species (Diagne et al., 2017; Tangprasittipap, Prasertsan, Choorit, & Sasaki, 2007). Altererythrobacter and Dyella were also to be related to biodegradation of aromatic compounds or halotolerance (Li et al., 2019; Qin et al., 2016; Zhang, Yang, & Wang, 2016; Zhao, Zhou, Jia, & Chen, 2010).…”
Section: Discussionmentioning
confidence: 99%